2012
DOI: 10.4025/actascianimsci.v34i3.12360
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of the cottonseed meal with or without addition of protease and phytase enzymes in swine diet

Abstract: This study evaluated the digestibility of cottonseed meal with or without addition of enzymes (phytase and protease) for growing pigs. It was used 18 barrows, housed in metabolism cages, distributed in a completely randomized design, standardizing body weight (bw) with average of 25.8 ± 3.6 kg, with three treatments and six repetitions. The treatments consisted of a reference diet based on corn and soybean meal, the second treatment with replacement of 30% of the reference diet by cottonseed meal without enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Hauschild et al (2008) avaliaram o efeito da inclusão de triticale sobre a digestibilidade de dietas para suínos com ou sem enzimas e encontraram maior disponibilidade de proteína na dieta com a adição de enzimas. Lorena-Rezende et al (2012), ao avaliarem a digestibilidade do farelo de algodão com ou sem protease e fitase, observaram melhora na digestibilidade da proteína bruta e menor eliminação do nitrogênio nas fezes pelos animais do tratamento com enzima. Os parâmetros sanguíneos séricos e plasmáticos não foram influenciados (P>0,05) (Tab.…”
Section: Resultsunclassified
“…Hauschild et al (2008) avaliaram o efeito da inclusão de triticale sobre a digestibilidade de dietas para suínos com ou sem enzimas e encontraram maior disponibilidade de proteína na dieta com a adição de enzimas. Lorena-Rezende et al (2012), ao avaliarem a digestibilidade do farelo de algodão com ou sem protease e fitase, observaram melhora na digestibilidade da proteína bruta e menor eliminação do nitrogênio nas fezes pelos animais do tratamento com enzima. Os parâmetros sanguíneos séricos e plasmáticos não foram influenciados (P>0,05) (Tab.…”
Section: Resultsunclassified
“…Ojewola et al [45] reported similar finding showing that manganese, potassium and copper increased as CSM supplementation increased in broiler ration. On the contrary, Lorena-Rezende et al [46] observed increased phosphorus digestibility when 30% CSM was supplemented with enzymes but in pigs. Increased enzyme supplementation promoted better digestibility of calcium and manganese by the birds.…”
Section: Apparent Ileal Digestibility Of Nutrientsmentioning
confidence: 91%
“…Similar N balance could be due to similar protein content of SBM and CSM used in the study and isonitrogenous concentrate mixtures fed to the animals. However, Lorena-Rezende et al (2012) reported that the diets containing cottonseed meal (30% replacement with control diet with or without enzymes) resulted in higher (P<0.01) amount of retained nitrogen as compared to control (corn and soybean meal) diet in barrows. Present finding is corroborated by Tripathi et al (2012) who reported no significant difference in N retention among lambs fed CSM and Bt-CSM diets replacing groundnut oil meal.…”
Section: Nitrogen Balancementioning
confidence: 96%